Sensory evaluation of palm sugar candy from Arenga sap water and agarwood leaves infusion using a 9-point hedonic scale - Wangiyana, I Gde Adi Suryawan; Kurnia, Nova; Triandini, I Gusti Agung Ayu Hari; Fatihatum, Fatihatum (Universitas Muhammadiyah Mataram, 2024)
Agarwood (Gyrinops versteegii) and sugar palm (Arenga pinata) are essential non-timber forest products from Lombok Island, Indonesia. This research aims to conduct a 9-point hedonic scale on palm sugar candy made from a formulation of agarwood leaves infusion and Arenga sap water with different proportions. Four formulations are used as a treatment in this research, including F1 (agarwood infusion: sap water=1:2), F2 (agarwood infusion: sap water=1:3), F3 (agarwood infusion: sap water=1:4), and F4 (agarwood infusion: sap water=1:5). The 9-point hedonic scale is used in this research range from 9 (Like extremely) to 1 (Dislike extremely). Four statistical approaches were used, including Kruskall-Walllis, Freidman, ANOVA-CRD, and ANOVA-RCBD. Duncan Multiple Range Test and spider chart analysis were also used as analytical tools. Respondents were evaluated in 4 parameters: appearance, aroma, taste, and texture. The result shows that treatment significantly affects numerical hedonic scores given by the respondents in all statistical approaches. F3 has the highest numerical hedonic score in aroma and taste parameters, while F4 has the highest appearance and texture parameters. However, based on the overall evaluation, F4 is the best formulation. It could be concluded that a mixture of agarwood leaves infusion and Arenga sap water with a proportion 1 of 5 was the best formulation to produce palm sugar candy with the highest sensory evaluation score based on a 9-point hedonic scale.